2021
DOI: 10.1530/joe-20-0444
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome, endocannabinoids and metabolic disorders

Abstract: Two complex systems are emerging as being deeply involved in the control of energy metabolism. The intestinal microbiota, with its warehouse of genes, proteins and small molecules, i.e. the gut microbiome; and the endocannabinoid system, with its recent extension to a more complex signalling apparatus including more than one hundred lipid mediators and fifty proteins, i.e. the endocannabinoidome. Both systems can become perturbed following bad dietary habits and during obesity, thus contributing to exacerbatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 113 publications
(119 reference statements)
4
61
0
Order By: Relevance
“…Studies most in the context of metabolic dysfunctions, already reviewed elsewhere [ 19 , 169 ], suggest cross-talk between the gut microbiome and the eCBome. However, the connection of the gut-brain axis and the eCBome in neurodegenerative diseases has never been deeply investigated but, considering the important role of these two systems in the physiopathology of the CNS, it is worth doing it.…”
Section: The Ecbome As the “Hidden” Player Between The Gut And The Brain In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Studies most in the context of metabolic dysfunctions, already reviewed elsewhere [ 19 , 169 ], suggest cross-talk between the gut microbiome and the eCBome. However, the connection of the gut-brain axis and the eCBome in neurodegenerative diseases has never been deeply investigated but, considering the important role of these two systems in the physiopathology of the CNS, it is worth doing it.…”
Section: The Ecbome As the “Hidden” Player Between The Gut And The Brain In Admentioning
confidence: 99%
“…Studies performed in both AD-like animal models and patients suggested that eCB system alterations are associated with AD pathophysiology, and that its pharmacological modulation may have disease-modifying effects [ 17 , 18 ]. In the last few years, the interconnection of the eCB system and the gut microbiota has been addressed and different aspects of regulation and dysregulation of the gut microbiome and eCB system mainly in obesity and metabolic disorders excellently reviewed [ 19 , 20 ]. Recently, the eCB system and the gut microbiota dysfunctions were also reported in neuropsychiatric disorders [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cannabinoid hypertonus would therefore lead to an impairment of gut permeability with an increased circulation of bacterial endotoxins, and a consequent stimulus in the synthesis and release of pro-inflammatory cytokines. A further consequence may consist in the increased transfer of these cytokines to the brain, by an increase in BBB permeability or even by transport through the afferent fibers of the vagus nerve (gut–brain axis) [ 302 , 303 ]. In fact, rimonabant, which antagonizes CB1R, reduces LPS levels and inflammation [ 304 ].…”
Section: Ecs and Gut Microbiomementioning
confidence: 99%
“…ECs have been found to be produced in adipose tissue, muscle (33,34), and kidneys (35), all of which are involved in the control of energy metabolism. Moreover, ECs are also produced in gut, and they in turn at a minimum influence hepatic function and signaling through the vagal afferents (25,(36)(37)(38)(39). Additionally, ECs are produced in stellate cells of liver (40) and islets of Langerhans: this review focuses on islets of Langerhans.…”
Section: General Background Of Ecs and Cbrsmentioning
confidence: 99%